(untitled) (Mantichora. Italian Journal of Performance Studies, 2024)
This article investigates the considerable anthropological and social value of Christiane Jatahy’s theater performance Depois do silêncio1. Jatahy, Brazilian playwright, director and actress, conducts in-depth analysis and a philological work on various documentary materials while also adapting literary and cinematic sources for the theatrical stage in a performance depicting the journey of the Brazilian Landless Workers’ Movement, descendants of slaves still persecuted today, and unveiling dark aspects of the history of Auriverde. This essay examines the play Depois do silêncio (After the Silence), the third and final chapter of the Trilogy of Horror, a performance in Portuguese in which we can observe this Wagnerian transmedia summa. The play gives the impression of leaning heavily towards documentary theater but, gradually, the static aspect of the beginning of the work fades away and the discussion unfolds among the three main characters, cinema intermingles on the stage and the live music by Aduni Guedes brings forth the sound of the earth, the celebration, the tribal rite and the magic spirits.